Analisis Putusan Tindak Pidana Asusila Terhadap Anak di Kabupaten Sidoarjo (Studi Kasus pada Pengadilan Negeri Sidoarjo) - Sari, Dwi Anita Puspita; Rosnawati, Emy (Indonesian Journal Publisher, 2024)
Lately, immoral acts involving children often occur, One of them is the number of case reports regarding rape, harassment, and so on. The immoral act of rape is one of the forms of violence against children. The purpose of this study was to determine the analysis of decisions on immoral crimes against children in Sidoarjo Regency. The research method used is normative juridical with a statutory approach. The results of this study show that there is a disparity between the decisions of one another in the 2019-2021 timeframe, both from the judge's considerations, decisions and other things. The benefit of this research is that the author hopes that this writing can be useful by providing knowledge and information to the public as a reference to find out how to analyze the decision on immoral actions against children in Sidoarjo Regency (Case Study at the Sidoarjo District Court). The analysis of the legal material used is deductive reasoning, what is meant by deductive reasoning analysis here is reasoning based on a mindset that has a general nature to draw conclusions on a specific nature.